1997
DOI: 10.1143/jjap.36.3635
|View full text |Cite
|
Sign up to set email alerts
|

The Nickel/Diamond(100)–(2 × 1)H Interface Studied with Electron Spectroscopy

Abstract: The nickel/diamond(100)–(2 ×1)H interface has been studied using Auger electron spectroscopy, electron energy loss spectroscopy and low-energy electron diffraction. Deposition of ultrathin nickel films at room temperature results in the formation of disordered nickel islands, whereas heteroepitaxial growth is achieved during deposition at 520 K. At temperatures above 850 K nickel interaction with the uppermost diamond layers causes graphitization of the diamond surface, a process which sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In this paper we demonstrate the growth of graphene layers using diamond (001) oriented substrate as a source for carbon in a PUC process. We prove that the catalytic reaction of nickel on diamond [27,29,30,31] enables the use of diamond as a carbon solid source for the fabrication of thin multilayer graphene films (see figure 1). Furthermore, we show that it is possible to combine this method with a Molecular Beam Deposition (MBD) [23] of carbon to enhance the quality of the graphene layers.…”
Section: Introductionmentioning
confidence: 63%
“…In this paper we demonstrate the growth of graphene layers using diamond (001) oriented substrate as a source for carbon in a PUC process. We prove that the catalytic reaction of nickel on diamond [27,29,30,31] enables the use of diamond as a carbon solid source for the fabrication of thin multilayer graphene films (see figure 1). Furthermore, we show that it is possible to combine this method with a Molecular Beam Deposition (MBD) [23] of carbon to enhance the quality of the graphene layers.…”
Section: Introductionmentioning
confidence: 63%
“…Graphitization on a bare monocrystalline diamond C(111) surface began at approximately 850 °C, 13 while for a bare monocrystalline diamond surface C(100) graphitization began at 1200 °C. 14 Monocrystalline diamond substrates with a large surface area for graphene-on-diamond technology would be too costly for commercial applications. However, nanocrystalline diamond (NCD) offers an alternative, chemically matched native platform for graphene synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Metals such as Ni, Cu, or Fe are used to melt or dissolve carbon atoms and, therefore, to reduce the graphitization temperature of a diamond surface significantly. In particular, a graphitization temperature as low as 247 °C has been reported on Ni/C(100) …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1(4), it is considered that the treatment would etch the Ni layer as well as diamond as reported previously. 25) As for our experiments, we could obtain the data on the Ni layer behavior after thermochemical-etching for the case of annealing at 800°C, which was estimated from surface profiles measured with a laser profiler before/after the Ni layer removal. As a result, it was found that the Ni layer thickness after thermochemical-etching was estimated to be about 0.8 « 0.1¯m, which was approximately 20 % thinner than that before the thermochemical-etching.…”
mentioning
confidence: 99%